Perancangan Sistem Informasi Point of Sale Berbasis Web untukManajemen Penjualan pada Peternakan Kambing - Sugandhi, Muhammad Fahri; Luthfi Firdaus, Rangga; Sanjaya, Wira; Fildzah, Malahati; Saputra, Vicky Aulia; Syarif, Zulkarnaen Noor (Teknik Informatika Fakultas Ilmu Komputer, 2026)
Micro, small, and medium enterprises (MSMEs) in goat farming continue to encounter challenges in sales management, livestock data recording, and financial reporting due to reliance on manual processes. These issues often result in recording errors, data inconsistencies, and difficulties in routine business performance monitoring. This research designs and develops GoatPOS, a web-based Point of Sale (POS) system to facilitate goat sales management, ready-to-sell livestock inventory, financial reports, and customer data. Research methods encompass observation, interviews, and literature review, with system development following the Waterfall model. A client-server architecture is employed, utilizing Node.js for backend business logic and API services, alongside React.js for the interactive frontend interface. Findings demonstrate that GoatPOS enhances operational efficiency through transaction automation and real-time reporting, while bolstering data security via role-based access control. Thus, GoatPOS emerges as an information system solution promoting data-driven decision-making and the sustainability of goat farming enterprises.